Pemberdayaan Masyarakat sebagai Upaya Pencegahan Covid-19 di Dusun Ngerong, Kecamatan Porong, Kabupaten Pasuruan: Pemberdayaan Masyarakat sebagai Upaya Pencegahan Covid-19 - Taqwanur; Mohammad Reza Afiyanto (Journal of Science and Social Development, 2021)
The Covid-19 pandemic in Indonesia has occurred since March 2020 until now which has had an impact on aspects of life such as health, economy, education and so on, so it is necessary to have a strategy for implementing community service involving lecturers and students of Nahdlatul Ulama University Sidoarjo with community leaders in the Hamlet. Ngerong, Gempol District, Pasuruan Regency. From the results of these discussions, several programs were made, namely, providing counseling and socialization about the dangers of covid-19, modes of transmission and methods of prevention, implementation of counseling and socialization carried out in limited numbers, door to door and posting posters on how to prevent the virus and providing information about vaccine schedules in the surrounding area and Pasuruan, conduct training (training) on ​​digital marketing (online sales) and assistance in the use of features on social media for MSMEs, provide tutoring and study face-to-face with very limited numbers and carry out health protocols properly .